2014
DOI: 10.9738/intsurg-d-13-00251.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Surgical Site Infection in Orthopedic Surgery: A 5-year Analysis

Abstract: Surgical site infection (SSI) is disastrous in orthopedic practice as it is difficult to rid the bone and joint of the infection. This study was aimed to assess the prevalence of SSI in orthopedic practice and to identify risk factors associated with surgical site infections. All patients admitted to the orthopedic male and female wards between January 2006 and December 2011 were included in the study group. The data, which were collected from the medical charts and from the QuadraMed patient filing system, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
101
6
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(124 citation statements)
references
References 22 publications
12
101
6
5
Order By: Relevance
“…The prevalence of SSI in the current study is higher than that reported by other authors 2,3,4,6,7,8,9,10 . However, similar prevalence of SSI was observed in other studies done by 1,12, .…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…The prevalence of SSI in the current study is higher than that reported by other authors 2,3,4,6,7,8,9,10 . However, similar prevalence of SSI was observed in other studies done by 1,12, .…”
Section: Discussioncontrasting
confidence: 55%
“…There is a direct relationship between development of surgical site infection and the length of surgery. Orthopaedic surgeries done for more than 2 hours are at higher risk of infection 3,7,10,11,12,13,14 . Similar finding was noted in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations